1970
DOI: 10.1139/f70-193
|View full text |Cite
|
Sign up to set email alerts
|

Preferred Temperature of Yearling Lake Trout, Salvelinus namaycush

Abstract: Preferred temperatures were determined for yearling lake trout acclimated to 5, 10, 15, and 20 C. Acclimation temperature had virtually no effect on preferred temperature. The final preferendum was 11.7 C, which is about 2 degrees C warmer than the temperature at which lake trout are most commonly caught in thermally stratified lakes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
14
0

Year Published

1977
1977
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(16 citation statements)
references
References 0 publications
2
14
0
Order By: Relevance
“…Using this technique, the final temperature preferendum for Anguilla rostrata was 16.7°C. It should be noted that other investigators have shown that acclimation temperature does not influence preferred temperature for certain salmonids (McCauley & Tait, 1970;Garside & Tait, 1958). …”
Section: Resultsmentioning
confidence: 86%
“…Using this technique, the final temperature preferendum for Anguilla rostrata was 16.7°C. It should be noted that other investigators have shown that acclimation temperature does not influence preferred temperature for certain salmonids (McCauley & Tait, 1970;Garside & Tait, 1958). …”
Section: Resultsmentioning
confidence: 86%
“…The combined expression of these multigenic traits among fish species during summer periods of thermal stratification, along with other environmental variables (Fry 1947), yields the temperature and depth distributions of predators and their prey. Numerous laboratory studies have contributed to our understanding of the thermal behavior of lake trout, including preferred temperatures (e.g., McCauley and Tait 1970;Peterson et al 1979;Edsall and Cleland 2000), optimum temperatures for growth (e.g., Elliott and Hurley 1999;Edsall and Cleland 2000), and temperature tolerance or lethal limits (e.g., Ihssen 1973;Grande and Andersen 1991). The temperature relationships described by these studies are consistent (Jobling 1981), which suggests that a component of temperature selection is genetic and defines the fundamental niche axis as defined by Hutchinson (1957).…”
mentioning
confidence: 84%
“…The range of temperature in the gradient was greater during winter testing; however, the difference was probably not responsible for the seasonal shift in thermal preference, since winter tested animals avoided temperatures greater than 28.9"C and less than ll.O"C. Inherent seasonal rhythms in temperature preference or thermal tolerance have been demonstrated for some species of fish (Sullivan & Fisher 1953, Hoar 1955, Tyler 1966, Kowalski et al 1978. Nevertheless, other investigators have found no significant inherent seasonal shift in the thermal preference of other fish species (McCauley & Tait 1970, Garside & Tait 1958, DeVlaming 1971, McCauley & Huggins 1979.…”
Section: Discussionmentioning
confidence: 95%